Strategi Pembinaan Karakter Berbasis Pancasila untuk Rehabilitasi Anak Binaan di Lembaga Pembinaan Khusus Anak Kelas Ii Bandung - Sulistijaningsih, Sri; Nurihsan, Juntika; Nurdin, Encep Syarief; Sabri, Muhammad; Munawir, Ahmad (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to identify character building programs and analyze obstacles in implementing character building programs for the rehabilitation of children in the Bandung Class II Special Children’s Rehabilitation Center. A qualitative descriptive approach was used to analyze Pancasila-based character building programs for the rehabilitation of children. The results of the study indicate that character development for the rehabilitation of juvenile offenders at the Bandung Class II Special Juvenile Rehabilitation Center is implemented through formal education programs as well as religious, intellectual, and national awareness character development programs, health, sports and arts, law and society, and independence. The challenges faced in character development efforts for the rehabilitation of juvenile offenders at the Special Juvenile Correctional Facility Class II Bandung include limited facilities and infrastructure, insufficient collaboration with educational institutions and local governments, a shortage of qualified educators and trainers, inadequate facilities, insufficient funding allocation, and poorly structured supervision. Efforts to address these challenges in character development for children in the Special Children’s Rehabilitation Center Class II Bandung can be achieved by improving human resource quality, enhancing facilities and infrastructure, optimizing budgets, fostering inter institutional collaboration, and developing a more structured evaluation system.